Design of a Rumah Budaya in the Context of Preserving Karo Culture in Desa Lingga, Karo Regency, North Sumatra - Nasution, Putri Handayani; Ginting, Salmina Wati (International Journal of Culture and Art Studies, 2023)
The Siwaluh Jabu Traditional House is one of the cultural heritages from the ancestors of the Karo people from the past. This traditional house is located in Desa Lingga (Lingga Village), Karo Regency, North Sumatra, Indonesia. The interest of tourists in visiting this traditional house has made the local government make Desa Lingga a cultural village. Traditional houses and other cultural heritage symbolize the greatness of the Batak Karo ancestors in the past. Nevertheless, the "remains" (inheritance) of greatness seems to have less attention anymore. This paper was created with the aim of examining the existence of cultural heritage with tourism potential of the Siwaluh Jabu Traditional House in Desa Lingga and providing architectural design solutions as a form of Karo Cultural preservation by creating a Rumah Budaya that provides lodging facilities and cultural learning facilities in order to preserve Karo Culture. The research was conducted using a qualitative descriptive method where the authors obtained the data by observing and describing th eenvironmental conditions of the object. Referring to the research results, it was found an idea for an design that has a cultural program where visitors and tourists can enjoy the atmosphere of Lingga Village, which is unique to its Karo Culture while learning about this culture. The design of this cultural learning facility will impact the Siwaluh Jabu Traditional House because this traditional house will experience preservation which is expected to lead to an increase in tourist visits to the Desa Budaya Lingga.